TEKNOLOGI JARINGAN DALAM CLOUD COMPUTING - Ali Ahmadi (STMIK Mardira Indonesia, Bandung, 2015)
Cloud computing is an alternative model of the implementation and utilization of services related to Information Technology. This paradigm is touted to simplify the way procurement and purchasing IT products by the buyer, and also lighten the load shipments by vendor. However, there are a number of risks and constraints to adopt this model. In general, the definition of cloud computing is a style of computing with a large number of IT services that are scalable presented in the form of 'service' to external customers using Internet technologies. This provides an alternative to the vendors in the supply of business services supported by IT. Cloud computing contains a number of basic concepts, namely grid computing, distributed network of servers, distributed virtualization, and a series of services concept is Software as a Service (SaaS), Platform as a Service (PaaS) and Infrastructure as a Service (IaaS) , and so on which became known as the terminology XaaS.Cloud computing relies heavily on Internet technology. Therefore, the network infrastructure is one of the cores of cloud computing implementations. This paper will attempt to examine the role of technology in the implementation of cloud computing network. Keywords: Cloud Computing, Network Technology, Service, Internet, Grid Computing Abstrak Cloud computing adalah suatu alternatif model penyelenggaraan dan pemanfaatan layanan-layanan terkait Teknologi Informasi. Paradigma ini disebut-sebut dapat mempermudah cara pengadaan dan pembelian produk-produk IT oleh pembeli, serta memperingan pula beban pengiriman oleh vendor. Bagaimanapun juga, terdapat sejumlah resiko dan kendala untuk mengadopsi model ini. Secara umum, definisi cloud computing adalah suatu gaya komputasi dengan sejumlah besar layanan IT yang bersifat scalable disajikan dalam bentuk 'service' bagi nasabah eksternal dengan menggunakan teknologi Internet. Hal ini memberikan alternatif bagi para vendor dalam memasok business services yang didukung oleh IT. Cloud computing mengandung sejumlah konsep dasar, yaitu grid computing, distributed network of servers, distributed virtualization, dan serangkaian services concept yaitu Software as a service (SaaS), Platform as a service (PaaS) serta Infrastructure as a service (IaaS), dan sebagainya yang kemudian dikenal dengan terminology XaaS.Cloud computing sangat bergantung pada teknologi internet. Oleh karena itu infrastruktur jaringan merupakan salah satu inti dari implementasi cloud computing. Paper ini akan mencoba menelaah peran teknologi jaringan dalam implementasi cloud computing. Kata kunci: cloud computing, teknologi jaringan, service, internet, grid computing